Agrarian Policy of the Region in Terms of Economic Development Innovation - Gridchina, Alexandra V.; Orekhova, Lyudmila L.; Lyubimtseva, Svetlana V.; Yakovenko, Nataliya V.; Komov, Igor V. (International Journal of Economics and Financial Issues, 2016)
The relevance of the topic lies in the difficult situation of the agricultural sector, which explains the General decline in production, broken economic ties, lack of scientifically grounded concept of legal base for implementation of market reforms, and innovation mechanism, creating economic conditions for expanded reproduction, which led to the deconstruction of all existing systems. The current situation in the agricultural sector is characterized by crisis factors. The main cause of imbalance of the system of agriculture was a radical transformation of the ownership of the means of production. Changed organizational-legal forms of collective enterprises, was developed the sector of individual entrepreneurship in rural areas. Agriculture with its labor-intensive production may allow one of the most acute social problems - employment. Consequently, there is the problem of the development of the mechanism of economic relations between the government, stakeholders in the agricultural production and commercial structures for the development of new adequate approaches to the provision of investment resources to the agricultural sector of the economy. Thus the expansion of the scope of economic methods of state return release of funds to the agricultural sector can become a real source of maintaining their resource potential as the most economical and effective innovative way to support the industry. Keywords: agriculture, innovations, innovation transformation, innovation process, food security JEL Classifications: Q18, R11, R58